Capsaicinoids in Chili Habanero by Flow Injection with Coulometric Array Detection. Issue 5 (6th February 2019) - Morozova, Ksenia; Rodríguez‐Buenfil, Ingrid; López‐Domínguez, Cindy; Ramírez‐Sucre, Manuel; Ballabio, Davide; Scampicchio, Matteo
Abstract: This study presents a sensitive electroanalytical method for the determination of capsaicinoids in chili extracts using flow injection with coulometric array detector. Flow injection method was developed based on the coulometric signal of capsaicinoids obtained by high performance liquid chromatography with coulometric detector (HPLC‐ECD). Capsaicinoids concentration in 18 chili samples from Yucatán México cultivated in different types of soils was quantified using UHPLC‐DAD and HPLC‐ECD and expressed in Scoville units. The plants were cultivated in a greenhouse on three types of limestone soils, namely, red, black and brown. Chili peppers were harvested in two stages of maturity: immature (green), and mature (orange). HPLC‐ECD method showed ten times higher sensitivity compared to the UHPLC‐DAD. Capsaicinoid content in 18 chili samples was measured by flow injection method. The best correlation with the Scoville units was obtained by the analysis of the current signal of the sensor poised at +450 mV (R 2 =94). ANOVA analysis showed that the soil type and the harvest date were significant for the capsaicinoid content. Chili plants cultivated in red soil had higher capsaicinoid content. In addition, the capsaicinoid content was increasing at later harvest dates. In summary, the suggested flow injection method with coulometric array detector decreased the time of analysis from 15 min to 30 s. Therefore it can be successfully applied for the routine capsaicinoid analysis in chili. Abstract :